A study of the gangotri glacier retreat in the himalayas using landsat satelite images. - Ambinakudige, S.
The retreat of glaciers is an indicator of climate change, and is rapid in the Himalayas. Multi-temporal satelite images are ideal for studying changes in glaciers in the rugged Himalayan landscape. In this study, Landsat (MSS. TM, ETM+) images were used to locate the position of the ice wall of the Gangotri glacier in 1976, 1979, 1990, 1999, 2006 and 2009. The results of image interpretations indicated that between November 1976 and February 2009, there was an average annual retreat of 22m in the ice wall's position. The straight line distance between the 1979 position and the 2009 position of the ice wall was about 700m. The cave of the glacier also changed its position longitudinally a few times over the study period. Fluctuations in the average monthly temperature and precipitation in the region during monsoon and winter seasons could have influenced the rate of recession of the Gangotri glacier.
Keywords: Gangotri glacier retreat